Muslim Society Perception of The Unregistered Divorce - Lutfi Lutfi; Muhammad Akbar; Marzuki Marzuki (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2020)
The aim of this paper is to discuss the view of Muslim people in Marawola, district of Sigi, towards unregistered divorce. This study uses qualitative methods and data was gathered through observation, in-depth interviews, and written material. Data analysis was analyzed using grounded theory approach. The results showed that the understanding and view of the Marawola community towards unregistered divorce was that of divorce carried out outside a religious court involving only husband and wife and religious leaders. On other occasions, it also involved village officials, where the divorce was only confirmed by a letter of freedom signed by the husband and wife, two witnesses and sometimes also signed by the village head as the one who knew.